A convenient diagnostic tool for discriminating adult-onset glutamic acid decarboxylase antibody-positive autoimmune diabetes from type 2 diabetes: a retrospective study - Sia,Hon-Ke; Tu,Shih-Te; Liao,Pei-Yung; Lin,Kuan-Han; Kor,Chew-Teng; Yeh,Ling-Ling (PeerJ, 2020)
Background The glutamic acid decarboxylase antibody (GADA) test, commonly used to diagnose autoimmune diabetes, is not cost-effective in areas of low prevalence. The aim of this study was to develop a convenient tool to discriminate adult-onset GADA-positive autoimmune diabetes from type 2 diabetes (T2DM) in patients with newly diagnosed diabetes. Methods This retrospective cross-sectional study, conducted at Changhua Christian Hospital in Taiwan, collected electronic medical record data from January 2009 to December 2018. Patients were divided into a case group (GADA+, n = 152) and a reference group (T2DM, n = 358). Variables that differed significantly between the groups were subjected to receiver operator characteristic analysis to establish cutoff values. Discriminant function analysis was then employed to discriminate the two groups. Results At the onset of diabetes, the GADA+ group was younger, with lower body mass index (BMI), higher hemoglobin A1c (HbA1c), higher high-density lipoprotein cholesterol (HDL-C), and lower total cholesterol and triglycerides (TG). Five major factors were identified to form the linear discriminant functions: BMI, age at onset, TG, HDL-C, and HbA1c. BMI < 23 kg/m2 was the most important factor, followed by TG < 98 mg/dL, HDL-C ≥ 46 mg/dL, age at onset < 30 years, and HbA1c ≥ 8.6%. The overall accuracy of the linear discriminant functions was 87.1%, with 84.2% sensitivity and 88.3% specificity. Conclusions Routine tests in diabetes care were used to establish a convenient, low-cost tool that may assist in the early identification of adult-onset GAD+ autoimmune diabetes in clinical practice.
Keywords: GAD antibody; Diagnosis; Autoimmune diabetes; Type 1; Type 2; Glutamic acid decarboxylase antibody; BMI; Triglycerides; Adult-onset diabetes; LADA